What Should be done to Avoid Plagiarism among University Students? - Syahrul Nizam, Junaini; Jonathan, Sidi (Academic Quality Synposium, 2007)
Plagiarism has become a serious concern for university administrator, lecturer, and course coordinator. With rapid development of the Web, more opportunities are presented for the student to commit such infringements. This widespread situation poses variety of threats especially for the academic institutions. This paper investigates this issue and proposes a holistic mean of addressing this concern. As a university lecturer, knowing how to educate your student to stop plagiarism from the start is crucial. This paper examines how to fight plagiarism of written assignment among university students.